Analisis Korelasi dan Kontribusi Pemanfaatan Waktu Belajar Mahasiswa Toraja Pendidikan Geografi Terhadap Hasil Belajar - Gitaris, Juita; Andaria, Kalvin Salindeho; Ramadhan , Muhamad Isa (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2023)
The research objective was to find out how using student study time improves learning outcomes. Data collection techniques with questionnaires, and observation. Data analysis techniques using descriptive statistics and inferential statistics to determine the correlation between the use of study time and learning outcomes. The results showed a relationship between time utilization and learning outcomes with a correlation of rcount 0.863 > rtable 0.413. Utilization of learning outcomes contributes 73.2% to improving learning outcomes. Based on the t-test, the coefficients (B) are 0.622 and the value (B) is 0.034 with Sig. 0.000, meaning that using study time has a positive effect (+0.034) on improving learning outcomes. Students from Toraja have the habit of making good use of their study time, such as doing assignments, always making time to study, and being good at managing their time.